Impact of environmental pollution and weather changes on the incidence of ST-elevation myocardial infarction. (2nd June 2020) - Biondi-Zoccai, Giuseppe; Frati, Giacomo; Gaspardone, Achille; Mariano, Enrica; Di Giosa, Alessandro D; Bolignano, Andrea; Dei Giudici, Angela; Calcagno, Simone; Scappaticci, Massimiliano; Sciarretta, Sebastiano; Valenti, Valentina; Casati, Rebecca; et al.
Abstract: Background: Environmental pollution and weather changes unfavorably impact on cardiovascular disease. However, limited research has focused on ST-elevation myocardial infarction (STEMI), the most severe yet distinctive form of acute coronary syndrome. Methods and results: We appraised the impact of environmental and weather changes on the incidence of STEMI, analysing the bivariate and multivariable association between several environmental and atmospheric parameters and the daily incidence of STEMI in two large Italian urban areas. Specifically, we appraised: carbon monoxide (CO), nitrogen dioxide (NO2), nitric oxide (NOX), ozone, particulate matter smaller than 10 μm (PM10) and than 2.5 μm (PM2.5), temperature, atmospheric pressure, humidity and rainfall. A total of 4285 days at risk were appraised, with 3473 cases of STEMI. Specifically, no STEMI occurred in 1920 (44.8%) days, whereas one or more occurred in the remaining 2365 (55.2%) days. Multilevel modelling identified several pollution and weather predictors of STEMI. In particular, concentrations of CO ( p  = 0.024), NOX ( p  = 0.039), ozone ( p  = 0.003), PM10 ( p  = 0.033) and PM2.5 ( p  = 0.042) predicted STEMI as early as three days before the event, as well as subsequently, and NO predicted STEMI one day before ( p  = 0.010), as well as on the same day. A similar predictive role was evident for temperature and atmospheric pressure (all p  < 0.05). Conclusions: The risk of STEMI is strongly associated with pollution and weather features. While causation cannot yet be proven, environmental and weather changes could be exploited to predict STEMI risk in the following days.